DNA amplification fingerprinting in coconut: protocol optimization and analysis of resistance to root (wilt) disease - K. Jayadev; M. K. Rajesh; K. Devakumar; Regi Jacob Thomas; R. V. Nair; V. A. Parthasarathy (International Coconut Community Journal, 2005)
Root (wilt) disease is a serious malady in coconut causing a loss of approximately 968 million nuts a year in India. Integrated management practices are the only suggested methods to reduce its effect to some extent, while the development of resistant varieties will offer a permanent solution for which concrete breeding efforts are required. Considering the long life cycle of coconut, selection of resistant varieties through conventional methods will be time consuming and laborious. Molecular markers offer numerous advantages over markers traditionally used in plant mapping and selective breeding. Here, we present the optimization of PCR conditions for DNA amplification fingerprinting (DAF) of coconut using arbitrary oligonucleotide primers. Three of the primers could detect variations between root (wilt) resistant and susceptible coconut palms. This study constitutes the basis for future efforts to tag the root (wilt) resistant gene(s) in coconut.